Pelatihan Make Up Artist ( MUA ) Menjadi Enterpreneur Bagi Mahasiswa Tata Rias Jurusan PKK FT UNM : id - Burhanuddin, Izmi; Syamsidah; Hading, St. Aisyah; Maida, A. Nur; Riwayani, Rika (Program Studi Sarjana Terapan PTM FT UNM, 2025)
This community servies activity aims to provide trainingon make up technique to become a professional Make Up Artist MUA, intended to develop the make up servies skills of students from the department Of Family Welfare Education Beauty Concenstration, Fakulty of Engineering, Universitas Negeri Makassar. With the increasing demand for MUA services for various events such as weddings graduations, and photo sessions, this skill holds great potential as a promising source of income. The results of the program show a sigbificant improvement in students understanding of professional make uo techniques and a higher motivation to start independent businesses in the beauty sector. It is expected that this activity will fosteran entrepreneurial spirit and expand students career prospects in the increasingly creative beauty services industry. Keywords: Make Up Training, Make - Up Artist, Entrepreneurship, students.